2007
DOI: 10.1590/s0102-05362007000300012
|View full text |Cite
|
Sign up to set email alerts
|

Produção de biomassa, acúmulo de nitrato, teores e exportação de macronutrientes da alface sob sombreamento

Abstract: Yield, accumulation of nitrate, content and export of nutrients of lettuce cultivated under shadeIn this experiment we evaluated the production, accumulation of nitrate, content and exportable mineral nutrient (N, P, K, Ca, Mg e S) of lettuce cultivars Regina and Verônica cultivated under two thermo-reflective screens (Aluminet®30%-O and Aluminet®40%-O), and a diffusive screen (ChromatiNet Difusor®30%). The trial was carried out in Viçosa, Minas Gerais State, Brazil. Seeds were sown in trays of 200 cells, unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
2
0
5
Order By: Relevance
“…Thus, in regions where solar radiation is high, it is recommended the use of meshes in protected environments to guarantee that the gerbera production is not affected by high temperatures, since these meshes provide shading to the plants and have properties that improve microclimatic conditions in this environment (AQUINO et al, 2007). It is desirable that the gerbera production occurs in a protected environment to achieve better productivity and quality of flowers, as well as it protects against rain, wind and reduces the attack of pests and diseases (GUISELINI et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in regions where solar radiation is high, it is recommended the use of meshes in protected environments to guarantee that the gerbera production is not affected by high temperatures, since these meshes provide shading to the plants and have properties that improve microclimatic conditions in this environment (AQUINO et al, 2007). It is desirable that the gerbera production occurs in a protected environment to achieve better productivity and quality of flowers, as well as it protects against rain, wind and reduces the attack of pests and diseases (GUISELINI et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(Castro et al, 2001). Porém, em plantas de alface (Aquino et al, 2007) e folhas de Setaria sphacelata (Castro et al, 2001) não foram observadas alterações nos teores de Ca com redução da intensidade luminosa e para caules de Andropogon gayanus o aumento dos níveis de sombreamento proporcionaram redução dos teores deste elemento (Castro et al, 2001).…”
Section: Resultsunclassified
“…Otto et al (2001b) reported that production under NW was greater than under NT for the Iceberg lettuce cultivar Tainá, possibly because they were a different cultivar of those used in this present experiment. For AL and CR nets, Aquino et al (2007) found that the canopy dry matters of the lettuce cultivars Regina (butterhead) and Verônica (crisp type) were less than the plants cultivated under NT, because the radiation was restricted by nettings.…”
Section: Resultsmentioning
confidence: 99%